AN ANALYSIS OF JARGON IN MASTERCHEF INDONESIA SEASON 5 - Dewi Nurmala (Fakultas Sastra UMN AL Washliyah, 2021)
The objective of this research was to know the jargon and the forms of jargon used in the conversation on Masterchef Indonesia Season 5 live on one of private television in Indonesia. The method used in this research was descriptive qualitative method. The source of the data from this research were words, phrases, sentences in the conversation script between the jury and the participants on Masterchef Indonesia Season 5. The result found in this research that jargon used by the jury and the participants were in English. Then, it was found that there were 37 data in the conversation.From 37 data, there 26 jargon in the form of words and 11 in the form of phrases.